Proyecto de factibilidad para la creación de una empresa de fabricación de coches para bebes y su comercialización en la ciudad de Quito - Carrera Vasco, Berenice del Carmen (2015)
The general objective of this is to conduct a feasibility study for the establishment of a company Making Cars for babies and Marketing in the City of Quito. the same that allowed the application of different methods and techniques that research allows, as the inductive method, the deductive method, synthetic analytical method, statistical method. The market survey conducted in the city of Quito, with a sample of 400 surveys; Weighted surveys have been analyzed and the results have been inferred then perform market analysis, determining the potential demand of 430,310 families a Real Application for 120,487 families, 27,471 cars Effective Demand for babies, The Offer of 21,456 cars for babies Unsatisfied demand and 6,015 cars for babies, which allowed us to determine that the project can and should be run by the results obtained in the analysis of demand, supply and marketing levels for this product. The unmet demand reflects the potential market that exists in the city of Quito for this product, with the following results: For the first year of life of the project is unmet demand: 6,015 cars for babies, of which the company will be Installed Capacity offering 5,760 cars for babies, but will serve 4,608 cars for babies representing Capacity Utilization Project, suitable equipment will be used, which will guarantee for quality service at reasonable prices. Project engineering process diagrams determining the characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures develops. Also an administrative study determined as a Limited Liability Company, and the functional organizational structure hierarchical levels such as the legislative level, advisor level, auxiliary level and operational level, as well as operating manuals, charts was performed; which served as a guideline for implementing a good organization. To implement the necessary investment company Haciende to $ 74,757.91, with a net worth of $ 39,757.91 and a bank loan of $ 30,000. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 108,267.87, which indicates that the project or investment is suitable. For this project IRR is 45.93%, this being satisfactory value for the project, the time it would take to recover the original investment would be 2 years 1 month and 17 days for this project, the sensitivity values are less than one, thus not affecting the project changes in costs and revenues increased 19.3% and diminished by 13.8%, respectively, ie the project is not sensitive to these changes